Physicochemical characterization and trait stability in a genetically diverse ex situ collection of pomegranate (Punica granatum L.) germplasm from Cyprus - Kyriacou, Marios C.; Ioannidou, Sotiroula; Nikoloudakis, Nikolaos; Seraphides, Nicos A.; Papayiannis, Lambros C.; Kyratzis, Angelos C. (My University, 2020)
Proximity to the center of origin and geographical isolation shaped a unique genetic diversity of pomegranate in Cyprus that constitutes a valuable resource for the crop. Physicochemical characters and trait stability were studied for three years in an ex situ collection of 29 pomegranate accessions from Cyprus. Accession signature traits with exceptional yearly stability were titratable acidity and the citrate/malate ratio. Overall, the Cypriot germplasm was characterized by juice of low anthocyanin content (x¯ = 20.6 mg/L) and moderate phenolic content (x¯ = 613.0 mg/L) with glucose (x¯ = 69.1 g/L) and fructose (x¯ = 74.2 g/L) as predominant sugars. Juice antioxidant capacity was associated primarily with total phenolics and less so with juice color and anthocyanin content. Total sugar content was higher in large-fruited accessions with darker juice. In most accessions the titratable acidity was low (<0.50% w/v), with citric (x¯ = 44.7%), malic (x¯ = 39.1%) and succinic (x¯ = 15.8%) being the main organic acid fractions detected. Based on the maturity index (SSC/TA), six accessions were sweet-sour or borderline sweet-sour and 23 accessions were sweet. Cluster analysis of phenotypic characteristics and genetic data revealed a core group of thirteen genetically and phenotypically close accessions constituting the Cypriot pomegranate landrace, characterized by moderate fruit weight, high juiciness, thin rind, moderately hard seeds and light-colored juice low in acidity, anthocyanins, phenolics and antioxidant capacity. The present work advances the understanding of genetic and environmental contribution to the configuration of pomegranate physicochemical fruit composition.
Keywords: Antioxidant activity; Anthocyanins; Genetic polymorphism; Organic acids; Phenolic compounds; Postharvest quality; Soluble carbohydrates; Texture analysis